2012
DOI: 10.1021/ic302011x
|View full text |Cite
|
Sign up to set email alerts
|

Isomer-Directed Structural Diversity and Its Effect on the Nanosheet Exfoliation and Magnetic Properties of 2,3-Dimethylsuccinate Hybrid Frameworks

Abstract: The structures of seven new transition metal frameworks featuring Mn, Co, or Zn and either the meso or chiral D and L isomers of the 2,3-dimethylsuccinate ligand are reported. Frameworks that exhibit two-dimensional covalently bonded layers with weak interlayer interactions can be made with all three cations by incorporation of the chiral isomers of the 2,3-dimethylsuccinate ligand. The formation of such structures, suitable for the creation of nanosheets via exfoliation, is, however, not as ubiquitous as is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…The solution-based exfoliation procedure is less effective in the neutral coordination polymers which can be completely delaminated (with a thickness ca. 1-1.5 nm) [115,170,[176][177][178][179][180][181][182][183]. The stronger interlayer interactions in these hybrid compounds compared with the weaker van der Waals interactions observed in neutral 2D coordination polymers could be responsible of the lower degree of exfoliation.…”
Section: Guests Intercalation Of Hydrogen-bond-supported Layersmentioning
confidence: 99%
“…The solution-based exfoliation procedure is less effective in the neutral coordination polymers which can be completely delaminated (with a thickness ca. 1-1.5 nm) [115,170,[176][177][178][179][180][181][182][183]. The stronger interlayer interactions in these hybrid compounds compared with the weaker van der Waals interactions observed in neutral 2D coordination polymers could be responsible of the lower degree of exfoliation.…”
Section: Guests Intercalation Of Hydrogen-bond-supported Layersmentioning
confidence: 99%
“…chains, ladders, layers), MOFs are natural candidate hosts for low-dimensional magnetism [18]. Indeed the magnetic response of a number of key MOF familiesincluding formates [19], oxalates [20], and succinates [21,22]-can be interpreted in terms of low-dimensional behaviour. However, nearly all of our collective understanding of magnetic order in MOFs is based on indirect experimental techniques, such as magnetic susceptibility, heat capacity, and dielectric constant measurements [19][20][21][22][23].…”
mentioning
confidence: 99%
“…Indeed the magnetic response of a number of key MOF familiesincluding formates [19], oxalates [20], and succinates [21,22]-can be interpreted in terms of low-dimensional behaviour. However, nearly all of our collective understanding of magnetic order in MOFs is based on indirect experimental techniques, such as magnetic susceptibility, heat capacity, and dielectric constant measurements [19][20][21][22][23]. Tb(HCOO) 3 is a notable exception: it is one of the few MOFs for which neutron scattering measurements have been used to characterise magnetic structure within both antiferromagnetic (T < T N 1.6 K) and paramagnetic (T = 3 K) regimes [24,25].…”
mentioning
confidence: 99%
“…Compared with those in (S)-1,h owever,t he structural parameters of the chain in (S)-2 are slightly different (Table 3). If the Co1, Co2, (6) . Them ost significant feature of the structure of (S)-2 is that each chain is connected to two other equivalent chains through 4,4'-bpy bridges, whereas in (S)-1 each chain is linked to four othere quivalents by 4,4'-bpy (Supporting Information, Figure S6).…”
Section: Crystals Tructures Of (S)-2 and (R)-2mentioning
confidence: 99%
“…However,t here are only ah andfulo fr eports on comparative studies of homochiral and racemic inorganic-organic hybrid materials or metal-organic frameworks (MOFs) so far. [5][6][7][8][9] In this aspect, am ajor challenge is to isolate single crystals of both the chiral and racemic speciesb ased on the same ligand, whichi so ften very difficult. Lin et al found that the interpenetration of MOFs can be controlled by using enantiopure or racemic bridging ligands that further affectt he pore size and framework rigidity.…”
Section: Introductionmentioning
confidence: 99%